2010
DOI: 10.1007/s10549-010-0777-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between MnSOD Val16Ala polymorphism and breast cancer risk: a meta-analysis involving 58,448 subjects

Abstract: Published data on the association between MnSOD Val16Ala polymorphism and breast cancer risk are inconclusive. To derive a more precise estimation of the relationship, a meta-analysis was performed. Medline, PubMed, Embase, and Web of Science were searched. Crude ORs with 95% CIs were used to assess the strength of association between the MnSOD Val16Ala polymorphism and breast cancer risk. The pooled ORs were performed for co-dominant model (Val/Ala vs. Val/Val, Ala/Ala vs. Val/Val), dominant model (Ala/Ala + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The discrepancy that occurred may be because our current study was based on a much larger sample size, allowing the more precise detection of the association. In the subgroup analysis by cancer type, we found a significant association between MnSOD Val16Ala polymorphism and elevated prostate cancer risk, and no significant association between this polymorphism and breast cancer, which were consistent with previous meta-analyses [ 131 , 134 137 ].…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy that occurred may be because our current study was based on a much larger sample size, allowing the more precise detection of the association. In the subgroup analysis by cancer type, we found a significant association between MnSOD Val16Ala polymorphism and elevated prostate cancer risk, and no significant association between this polymorphism and breast cancer, which were consistent with previous meta-analyses [ 131 , 134 137 ].…”
Section: Discussionsupporting
confidence: 92%
“…the association between MDP and BC does not depend on SNP genotypes and vice versa. Associations between BC risk and the MnSOD SNP were found to be not statistically significant, which is in agreement with previous meta-analyses [19,[29][30][31]. For the association between the CAT SNP and BC risk, no meta-analyses were conducted.…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, Qiu et al [19] and Eras-Erdogan et al [20] reported no association. Therefore, it would be interesting to study the correlation between MnSOD gene polymorphism and its enzymatic activity in benign and malignant human breast tissue, which may clarify the role of MnSOD in breast cancer progression.…”
Section: Introductionmentioning
confidence: 99%